(untitled) (Journal of history, 2020)
In the article mentioned political, social, economical development and changes of Kazakhstan in the beginning of 20th century. A new stage in the history independent nation after royal crush. New development steppes in all spheres of Kazakh society has represented. It was main problem of that time. Autor considered some information about land and water reform. For Soviet Government main political problem to chose in national areas was land cases. The consequence of the colonical policy of the King’s government had aggraded the social economic situation of people. At the reform had been admitted of blunders and excesses. In some cases, poor men and migrants had been deprived of their lands. The migrants often had been involved to marrowbones and provided in national disagreement between Kazakh and migrants. Key words: modernization, proletariat, land reform, kolkhoz, state farm.